PENGARUH PEMBIAYAAN SYARIAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2019-202 - Helmiati, Helmiati; Kasmawati, Kasmawati; Putri, Febriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to examine the influence of murabahah, mudharabah and musyarakah financing on the profitability of Sharia Commercial Banks in Indonesia in 2019-2023. Samples were taken using a purposive sampling method, totaling 10 companies. Based on the simultaneous test results Murabahah, Mudharabah and Musyarakah have a significant effect on Profitability. While partially Murabahah, Mudharabah and Musyarakah financing also have a significant effect on profitability. The contribution of the independent variable to the dependent variable is 54,7% and the remaining 45,3% is influenced by other variables not included in this research. Hypothesis testing was carried out using multiple linear regression using SPSS 25.